PELATIHAN BAHASA INGGRIS UNTUK ANAK-ANAK DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KELAS II PANGKALPINANG - Septiawan, Yudi; Perkasa, Eza Budi; Fitriyani, Fitriyani; Diviana, Bonsarika; Dewi, Maretta Kusala (Jurnal Abdi Insani, 2024)
Education is the spearhead of a nation's progress. To succeed in life, a person must have an education because skills will be born. It motivated the author and team to conduct community service activities, especially English training for foster children at the Special Child Development Institution (LPKA) Class II Pangkalpinang. So far, foster children have only received written material (theory) yet to be practised. In addition, the media for delivering the material still needs to support learning activities. Community service activities in English training are present for foster children at LPKA Class II Pangkalpinang so they can learn practical English. In addition, strengthening English skills can be their capital in the future. This training uses a direct practice method and collaborates with the English community. Meetings are held every week and continue once a month. The material taught is about everyday conversation. From several training meetings, students were very enthusiastic about learning practice. Some foster children have even been able to practice speaking in English, introducing themselves well without looking at the text. This training continues to this day. There is a significant change in the foster children's abilities because the author and team use technological tools to deliver. It becomes one of the determining factors for the foster children's learning success.